PENERAPAN CORPORATE GOVERNANCE UNTUK KEPUTUSAN PENDANAAN PADA PERUSAHAAN MULTINASIONAL DAN NON MULTINASIONAL - Lydia I Kumajas (Tasharruf: Journal Economics and Business of Islam, 2017)
Abstract            The purpose of this research was to compare the implementation of the corporate governance. The comparison are between the companies which the controlling shareholders is a multinational company (group one) and non multinational company (group two), whether in the period before the economic crisis and the period during the economic crisis. Corporate governance is measured by perspective corporate financing decision (DER as a proxy).             This research uses samples in a manufacturing company which listed on the Indonesian Stock Exchange. The number of samples is 52 companies, which are divided into 30 companies as a group one and 22 companies in a group two. Observation period was 2006 to 2007 as the period before the crisis and 2008 as a period during the crisis.               The result of this research indicated companies in group one had a lower DER than firms in group two in period of crisis. In other word group one has better implementation of corporate governance than group two.